Hella Freud Bernays papers - Bernays, Hella Freud, 1893-1994.
Correspondence, autobiographical sketch, and printed material. Chiefly family correspondence including letters from Bernays's father Ely Bernays, mother Anna Freud Bernays, cousins Martin Freud and Oliver Freud, and sister Judith Bernays Heller. Other correspondence consists of letters from psychoanalysts in New York, N.Y., responding to Bernays's search for research, translation, and editorial work.
Editor and niece of Sigmund Freud.
Collection material in English and German.
Forms part of: Sigmund Freud collection.
Keywords: Bernays, Anna Freud, -- 1858-1955 -- Correspondence; Bernays, Ely -- Correspondence; Freud, Martin -- Correspondence; Freud, Oliver, -- 1891-1969 -- Correspondence; Freud, Sigmund, -- 1856-1939.; Heller, Judith Bernays -- Correspondence; Bernays family -- Correspondence; Freud family -- Correspondence; Psychoanalysis; Editors